Hypophosphatemia: mouse model for human familial hypophosphatemic (vitamin D-resistant) rickets. - Eicher, E M (1976)
A new dominant mutation in the laboratory mouse, hypophosphatemia (gene symbol Hyp), has been identified. The Hyp gene is located on the X-chromosome and maps at the distal end. Mutant mice are characterized by hypophosphatemia, bone changes resembling rickets, diminished bone ash, dwarfism, and high fractional excretion of phosphate anion (low net tubular reabsorption). Phosphate supplementation of the diet from wearning prevents the appearance of severe skeletal abnormalities. The hypophosphatemic male mouse resembles human males with X-linked hypophosphatemia and the Hyp gene is presemably homologous with the X-linked human gene. The mouse model should facilitate study of the defect in transport of plasma inorganic phosphate anion.